2015
DOI: 10.1093/nar/gkv858
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of promoter occupancy by the SND1 transcriptional coactivator identifies downstream glycerolipid metabolic genes involved in TNFα response in human hepatoma cells

Abstract: The NF-κB-inducible Staphylococcal nuclease and tudor domain-containing 1 gene (SND1) encodes a coactivator involved in inflammatory responses and tumorigenesis. While SND1 is known to interact with certain transcription factors and activate client gene expression, no comprehensive mapping of SND1 target genes has been reported. Here, we have approached this question by performing ChIP-chip assays on human hepatoma HepG2 cells and analyzing SND1 binding modulation by proinflammatory TNFα. We show that SND1 bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 77 publications
5
27
0
Order By: Relevance
“…In support of our data, Arretxe et al (25) showed that SND1 was potentially able to recognize the promoter region of SLUG through ChIP-on-chip assays. In our previous study, we likewise found that SLUG is a target promoter of SND1 by ChIP-guided ligation and selection assay (17).…”
Section: Snd1 Activates Slug Transcription By Increasing Chromatin Acsupporting
confidence: 90%
“…In support of our data, Arretxe et al (25) showed that SND1 was potentially able to recognize the promoter region of SLUG through ChIP-on-chip assays. In our previous study, we likewise found that SLUG is a target promoter of SND1 by ChIP-guided ligation and selection assay (17).…”
Section: Snd1 Activates Slug Transcription By Increasing Chromatin Acsupporting
confidence: 90%
“…However, pdTp treatment also resulted in a decrease in total p65 level indicating that SND1 regulates not only NF-κB activation but also p65 expression. Inflammatory cytokines induce SND1 expression and SND1 promoter contains consensus NF-κB binding sites (38,39). Thus chronic inflammation preceding HCC might result in induction of SND1 which facilitates expansion of TICs and further aggravates inflammation thereby establishing a scenario for the development of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid synthesis of lipids is required for generation of biological membranes and facilitating cancer cell proliferation. SND1 induction with TNFα and subsequent profiling of SND1 promoter activity revealed that SND1 regulates a group of glycerolipid metabolic genes including CHPT1, LPGAT1, PTDSS1 and LPIN1 that are involved in biosynthesis of phophatidylcholine, phosphatidylglycerol, phosphatidylserine and triacylglycerol respectively [58] . SND1 interacts with and inhibits monoglycerolipid lipase (MGLL) [41] , a tumor suppressor that converts monoglycerolipids to glycerols and free fatty acids.…”
Section: Role Of Snd1 In Lipid Metabolismmentioning
confidence: 99%